PERANAN CITRA DESTINASI DAN FAMILIARITY TERHADAP LOYALITAS WISATAWAN MANCANEGARA BERKUNJUNG KE BATAM - Hepy Hefri Ariyanto (LLDIKTI Wilayah X, 2019)
Tourism is something that is abstract, is not visible (by naked eye) can only be felt, moreover, tourism is actually a concept to be realized in everyday life. World tourism began to see people especially those bored with the routine of the city, and wanted to release the fatigue. Batam is a city with a very strategic location. Besides being in the international shipping lanes, the city has a short distance to the Singapore and Malaysia. Batam is part of the three major contributors to the numbers of tourist arrivals in Indonesia after Bali and Jakarta. The purpose of this study was to determine whether the destination image, familiarity and overall satisfaction affect the destination loyalty. Population of this research are foreign travelers in Batam, with a total sample of 399 respondents. Criteria samples used in this study was non probability convenience sampling method. Data analysis method used is multiple regression. Results from this study indicate that the destination image, familiarity, and overall satisfaction affect the destination loyalty.